Description of the Independency of the Elderly in Fulfilling Daily Living (ADL) Activities at the Cinta Kasih Tzu Chi Cengkareng Flat - Desi Hartati Silaen; Mey Lona Verawaty Zendrato (Journal of Global Research in Public Health, 2022)
Elderly people (elderly) experience a decrease in physical condition which affects the decline in activity, health and independency. Objective of this study to see an overview of the level of independency of the elderly in fulfilling the ability of daily activities (ADL). The research was conducted on the elderly at Tzu Chi Cengkareng Flat, West Jakarta during January-March 2022 with a survey method research design with a cross-sectional approach to 103 elderly people. Collecting data by direct interviews. Descriptive analysis to explain the characteristics of the independency of the elderly. The elderly in the Cengkareng Tzu Chi Love Flat are aged between 60-74 years, 97 people (94.2%), more than 75 years, 6 people (5.8%), female, 57 (55.3%) more than men. 46 (44.7%), more did not work 70 (68.0%) than those who worked 33 (32.0%) and had comorbidities, 62 people (60.2%) were elderly who had comorbidities. Of the 103 elderly, 101 (98.1%) had high independency and 2 (1.9%) had low independency. Conclusion  the elderly in the Tzu Chi Love Flat, are able to meet their daily needs without the help of other family members, more than 50% of the elderly are categorized as having high independency.